(untitled) (The Batuk, 2023)
The measurement of direct and diffuse solar radiation is not easily possible because instruments are quite expensive. The main objective of this study was to predict direct solar radiation (IB) and diffuse solar radiation (ID) on Pokhara (28.186643o N, 83.97518o E, 800 m asl) for a period of one year (2017). Daily data of spectral Aerosol optical depth (AOD) and total ozone column are obtained from NASA website. The maximum value of direct solar radiation and diffuse solar radiation values were found 932.9 ± 65.9 W/m2 in January and 363.0 ± 87.9 W/m2 in February respectively. The minimum value of direct solar radiation and diffuse solar radiation values were found 692.8 ±142.0 W/m2 in April and 107.7 ± 20.4 W/m2 in July respectively. The diffuse solar radiation changes with season. The annual average of direct solar radiation and diffuse solar radiation are found 808.1± 133.7 W/m2 and 220.8 ± 102.8 W/m2 and respectively. The results of this research work will help further identification, impact and analysis of solar radiation in different locations in Nepal with the same geographic conditions.